Kazakhstani Teachers’ Perceptions of Teacher Autonomy - Imangaliyev, Nurlan (Nazarbayev University Graduate School of Education, 2019)
Within the last decade Kazakhstan’s education system has undergone a number of major changes and reforms. These changes and reforms have had a massive effect on the teachers, as most of them had to undergo months of qualification courses and professional development workshops. In addition to current work overload, rising teacher turnover and decreasing influx of new teachers, this extra responsibility might affect teachers’ motivation and job satisfaction. As teachers are the ones who act as the agents of the educational reforms and changes, the question of whether the teachers are allowed sufficient autonomy and freedom in making certain decisions arises. A number of studies have revealed a strong link between teacher autonomy and job satisfaction and motivation. Moreover, research shows that the teachers’ perception of their own autonomy, rather than actual autonomy, also has a substantial effect on their willingness to stay in teaching profession. This mixed-methods study aims to reveal perceptions of individual teachers of their own autonomy and to explore any links of teacher autonomy to job satisfaction and motivation. Nine teachers from three different schools were interviewed for the qualitative part of the research. The three schools are different in the way they are governed internally: a private school, a public mainstream school and a charter school. For the quantitative part of the study 131 teachers from the aforementioned three schools took part in an online survey with closed questions. The qualitative part of the study helps us understand the teachers’ understanding of teacher autonomy and how it affects their practices and beliefs. Using the data gathered from the quantitative part of the study I attempted to establish any existing links between teacher autonomy and job satisfaction and motivation. In addition, the data helps us compare how teachers from schools with different institutional autonomy perceive their individual autonomy, or service autonomy.